Efektifitas Program Praktek Shalat Jenazah dalam Meningkatkan Pemahaman Siswa pada Pembelajaran Pendidikan Agama Islam Materi Shalat Jenazah di SMA Negeri 2 Gowa - Sugiyantoro Sugiyantoro; Idi Warsah; Hendra Harmi (Pusat Riset dan Inovasi Nasional, 2024)
The title of this research was taken from a background regarding the effectiveness of funeral prayer practice activities in increasing students' understanding of Islamic jurisprudence learning about funeral prayer material at SMA Negeri 2 Gowa. In this practical activity of funeral prayers, students are expected to be able to better understand the material about funeral prayers and be able to practice them in daily life properly and correctly. The aim of this research is to find out clearly about the effectiveness of funeral prayer practice activities to assess students' understanding in learning Islamic jurisprudence on funeral prayer material at SMA Negeri 2 Gowa. This research is a researcher who uses a correlation method with a quantitative approach and uses data collection techniques including interview, observation and documentation methods. Using data analysis techniques, namely percentage (%) and product moment. From the data analysis, it can be concluded that the practice of funeral prayers is effective in assessing students' understanding in learning Islamic jurisprudence regarding funeral prayers at SMA Negeri 2 Gowa. Which shows strongly, this is proven by analysis of statistical data, it can be seen that the effectiveness of funeral prayer practice activities to assess students' understanding in learning jurisprudence on funeral prayer material at Madrasah Aliyah Negeri Surabaya is in the very good and effective category. This can be seen from the assessment of the practice of funeral prayer activities with a calculation result of 95.2%. Meanwhile, students' understanding of the material on funeral prayers was 83.9%, and the effectiveness of the practice of funeral prayers to assess students' understanding of the material on funeral prayers was 2.518%.